Effect of GO nanosheets on microstructure, mechanical and fracture properties of cement composites. (26th December 2022) - Vantadori, Sabrina; Magnani, Giacomo; Mantovani, Luciana; Pontiroli, Daniele; Ronchei, Camilla; Scorza, Daniela; Sidoli, Michele; Zanichelli, Andrea; Riccò, Mauro
Highlights: Effects of GO nanosheets addition in a cement-based material are investigated. Both plain mortar and 0.03% GO reinforced mortar specimens are considered. The GO is obtained through the oxidation of graphite by using the Brodie's method. Chemical/structural material characterisation is carried out with XRD and SEM. Mechanical/fracture properties are obtained with flexural/compressive/fracture tests. Abstract: The aim of the present paper is to investigate the effects of graphene oxide (GO) nanosheets addition in a cement-based material from both a microstructural and a mechanical/fracture point of view. In particular, an experimental campaign is performed on both plain mortar and mortar reinforced with 0.03% GO nanosheets, obtained through the Brodie's method. The chemical and microstructural characterisation of the above materials is carried out by employing X-ray powder diffraction and SEM-EDS analyses, whereas the mechanical properties and fracture toughness are determined through flexural, compressive and fracture tests.